Evaluation of maize (Zea mays) cultivars under mixed rainfed cropping system at high altitude - Bandyopadhyay, B B (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2002 and 2003 to evaluate genetically dierent 7 populations of maize (Zea mays L.) cultivars under monoculture system and in association with bean at high altitude. Relative performance of prolificacy index, kernel weight, grain and fodder yield were examined. Maize cultivars showed significant genotypic variation for all traits but the differences between the 2 cropping system did not appear significant. The cultivation of maize for cobs was found more economical and stable than to grow for grain production. Correlation study indicated that selection for superior cultivars could be practised on the basis of prolificacy index, however, for the development of sustainable agriculture at high hills and to bring integration among crop and animal product genetic improvement in quality and quantity of maize fodder should be considered.